CONTRIBUTION OF THE PRINCIPAL IN THE IMPLEMENTATION OF MERDEKA BELAJAR AT SMK NEGERI 2 MANAJEMEN DAN BISNIS JAYAPURA - Desy Anita Karolina Sembiring; Agnes Aryesam (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2024)
This study aims to examine the contribution of the principal in implementing the Merdeka Belajar Curriculum at SMK Negeri 2 Manajemen dan Bisnis Jayapura, through an in-depth exploration of the principal's leadership role in creating an innovative and collaborative learning environment, relevant to the needs of the Society 5.0 era. The research locus is SMK Negeri 2 Manajemen dan Bisnis Jayapura. The research method used is descriptive qualitative with a case study approach. Data were collected through in-depth interviews, observations, and documentation. The research participants included the principal, the vice principal of curriculum, and several teachers actively involved in implementing the Merdeka Belajar Curriculum.The research results show that the principal's leadership significantly contributes to the successful implementation of the Merdeka Belajar Curriculum. The principal successfully created a learning environment that supports innovation and creativity by providing continuous training for teachers, encouraging collaboration among teachers, and involving parents and the community in school activities. The principal also managed to overcome resistance to change and resource limitations through effective and communicative leadership strategies. In conclusion, the principal's contribution to implementing the Merdeka Belajar Curriculum at SMK Negeri 2 Manajemen dan Bisnis Jayapura is highly significant. Through visionary and inclusive leadership, the principal has succeeded in improving the quality of education and preparing students to face challenges in the era of globalization and contribute positively to society.